From the pharaohs of Egypt to Manchester 2011, cough; remember a very old disease. (18th April 2012) - Thurlwell, ZR; Rice, C
Abstract : Tuberculosis (TB) is a disease of great antiquity, yet remains an important cause of mortality and morbidity across the globe. The national incidence of TB diagnosed in pregnancy was 4.2 per 100, 000 maternities in 2005-6. In the latest CMACE report, 266 cases and two indirect maternal deaths, were due to TB. The cases with maternal death were diagnosed late, possibly due to a lack of awareness among obstetric staff. We report a case of TB diagnosed at 34 weeks gestation. The 36 year old Sub-saharan African G3P2 lady had resided in the UK for 10 years and not travelled abroad. She developed gestational diabetes, which was tablet controlled. At 29+5, whilst attending a clinic appointment, she complained of fevers and an intermittent cough. Chest examination was clear and Chest X-ray (CXR) revealed no focal consolidation. A sputum sample was rejected as it was labelled incorrectly. She was treated with IV antibiotics and sent home. She re-presented at 33 weeks with pyrexia, cough and abdominal pain. The CXR now showed miliary TB. She had three negative sputums but early morning urine revealed mycoplasma. TB treatment was initiated on 34+5. She ruptured her membranes at 35+0 and had a spontaneous vaginal delivery at 35+1 with a 3.08 Kg baby. Baby was discharged on Day 4. Pregnancy and gestational diabetes are immuno-compromised states. A new persistent cough requires intensive investigation for TB including sputum, urine collections and if necessary bronchoscopy. Despite a missed opportunity for the diagnosis, outcome remained good.